Analysis Of Spending Standards And Assessment Of The Fairness Of Regional Spending Budget At The Office Of Investment And One-Door Integrated Services (DPM-PTSP) Of Jambi Province - Gowon, Muhammad; Yustien, Reni; Putri, Sasvira Ismiradita (Jurnal Cakrawala Akuntansi, 2023)
This study aims to analyze the standard spending and assess the fairness of regional spending budgets at the Office of Investment and One-Stop Integrated Services (DPM-PTSP) of Jambi Province. Focusing on three key activities—Formal Education and Training, Monitoring and Evaluation, and Investment Development—the research employs a Standard Spending Analysis (ASB) approach using a simple linear regression model. Secondary data from the 2016–2019 Budget Implementation Documents (DPPA) were analyzed with SPSS software to determine budget accuracy and fairness. The findings reveal varying levels of budget accuracy: Formal Education and Training experienced both overfinancing and underfinancing, Monitoring and Evaluation showed inconsistency, and Investment Development was consistently underfinanced. However, the fairness analysis suggests that most allocations fell within reasonable limits based on ASB calculations. These results highlight the importance of evidence-based budgeting in enhancing the efficiency, effectiveness, and accountability of regional financial management. The study recommends the integration of ASB frameworks into budget planning processes to minimize inefficiencies. Future research should explore broader regional contexts and include performance-based indicators to evaluate the impact of budget fairness on public service delivery.